2022
DOI: 10.1155/2022/7150204
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Efficacy Analysis of Biofeedback Electrical Stimulation Combined with Doxycycline in the Treatment of Type IIIA Chronic Prostatitis

Abstract: Purpose. To analyse the clinical efficacy of biofeedback electrical stimulation combined with doxycycline in the treatment of type IIIA chronic prostatitis. Methods. Eighty patients who met the diagnostic criteria of type IIIA chronic prostatitis in our hospital between February 2020 and February 2022 were selected and equally divided into the drug group and electrical stimulation group according to the random number table method. The drug group was treated with medication alone for 4 weeks; the electrostimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…For the treatment of prostatitis, the safer and more suitable alternative lies in gentle rectal drug delivery [ 21 , 22 ]. On the one hand, the prostate gland is adjacent to the rectum with rich venous plexus and lymphatic network traffic; on the other hand, rectal administration can avoid the first-pass effect and act directly on the prostate gland, increasing the local drug concentration and promoting the dissipation of inflammation in the glandular tissue [ 23 , 24 ]. To ensure effective drug retention in the rectal area and perfect delivery to the prostate, we selected two materials, lactoferrin (LF) and thermosensitive hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…For the treatment of prostatitis, the safer and more suitable alternative lies in gentle rectal drug delivery [ 21 , 22 ]. On the one hand, the prostate gland is adjacent to the rectum with rich venous plexus and lymphatic network traffic; on the other hand, rectal administration can avoid the first-pass effect and act directly on the prostate gland, increasing the local drug concentration and promoting the dissipation of inflammation in the glandular tissue [ 23 , 24 ]. To ensure effective drug retention in the rectal area and perfect delivery to the prostate, we selected two materials, lactoferrin (LF) and thermosensitive hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%